Survey on weedy rice (Oryza spp.) management practice and adoption of Clearfield® rice technology in Peninsular Malaysia - Dilipkumar, Masilamany; Ahmad Hamdani, Muhammad Saiful; Rahim, Hairazi; Chuah, Tse Seng; Burgos, Nilda Roma (Cambridge University Press, 2021)
A total of 452 rice farmers from three main granary areas of Muda Agricultural Development Authority (MADA), Kemubu Agricultural Development Authority (KADA), and Integrated Agricultural Development Area Barat Laut Selangor (IADA BLS) were surveyed in 2019. The goal was to determine farmers’ knowledge of and management practices for weedy rice (Oryza spp.) as well as the adoption level of Clearfield® rice technology (CRT) in Malaysia. Most farmers (74%) were adept at recognizing weedy rice. The majority of farmers (77%) perceived transplanting and water seeding rice systems as the best options to manage weedy rice, while only 10% of the farmers adopted CRT. The low level of adoption of this technology was due to several constraints, including the high cost of the CRT package and occurrence of imidazolinone (IMI)-resistant weedy rice in their farms. Farmers from MADA and IADA BLS reported the occurrence of IMI weedy rice in their farms for more than nine planting seasons, whereas those from KADA reported having resistant weedy rice for five to six planting seasons. The main factor contributing to the evolution of IMI-resistant weedy rice was ignorance about the technology and deliberate disregard of stewardship guidelines. The survey revealed that there is a need to increase awareness about CRT through training and educational programs for proper adoption of this technology.